READING TEACHING STRATEGIES APPLIED BY ENGLISH TEACHERS IN SENIOR HIGH SCHOOL - Tina Pandiangan; Sinta Parulian Lumban Gaol; Erikson Saragih (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2021)
Reading is an activity of observing written language which aims to gain knowledge or messages conveyed by the author. Many students have difficulty in reading and understanding the reading text. By knowing the factors that cause students' difficulties in reading. This proves that not all students can read well. This is due to the tendency of some teachers not to use teaching strategies appropriately. For this reason, this paper was created to explain what strategies in teaching reading are suitable for teachers to apply to students. The data was obtained by giving a questionnaire in the form of a Google form to 10 respondents who were English teachers who taught in senior high school. The data collection technique of this research is a questionnaire containing 10 questions. The results of the data analysis show that there are several techniques used by teachers in teaching reading strategies, namely Scanning, Skimming, Active Reading, Speed Reading, Structure-Proposition-Evaluation, and Survey-Question-Read-Recite-Review. However, not all students can accept and understand these teaching techniques. In this context, the teacher must be able to provide teaching strategies that are in following the interests and abilities of students. Adjustment strategies affect students' ability to follow lessons. The ability of teachers to combine more than one strategy is required to be able to help their students to be skilled at reading well in English.